THE ROLE OF COMPUTATIONAL THINKING IN IMPROVING HIGH SCHOOL STUDENTS’ PROBLEM-SOLVING ABILITIES - Febri Pramudya Wardani (JIPOWER : Journal of Intellectual Power, 2025)
This study investigates the role of computational thinking (CT) in enhancing the problem-solving abilities of high school students within the context of 21st-century education demands. Computational thinking, comprising skills such as decomposition, pattern recognition, abstraction, and algorithmic design, has emerged as an essential cognitive approach for tackling complex and ill-structured problems. Using a mixed-methods design, data were collected from 120 high school students through problem-solving tests, computational thinking assessments, and semi-structured interviews. Quantitative analysis using paired t-tests revealed a statistically significant improvement in students’ problem-solving performance after the integration of CT-based instructional strategies (p < 0.05). Qualitative findings further indicated that students demonstrated greater confidence, systematic reasoning, and adaptability when addressing both academic and real-life problem contexts. The results underscore the importance of embedding CT into high school curricula, not only as a digital literacy skill but also as a transversal competency that supports creative and analytical thinking. This study contributes to the growing body of evidence advocating for CT integration as a means to prepare students for higher education, STEM careers, and complex challenges in the digital era.